1998
DOI: 10.2514/2.384
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Effects in Sublaminate-Level Scaled Composite Laminates

Abstract: A series of tensile tests has been performed to determine the effect of specimen size on the mechanical response of composite laminates that were scaled at the sublaminate level. The two material systems studied were AS4/3502 and APC-2. In the case of AS4/3502, three generic layups were considered: [±30/90 2 L,, [±45/0/90]™, and [90/0/90/0]™ deg, where n = 1, 2, 3, or 4. For the APC-2 system, only the [±45/0/90],,.? deg layup was studied with n = 1 and 4. The effect of specimen size was examined with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many articles [33,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] showed that stacking sequence is a key parameter in scaling composite materials. There are three scaling approaches, namely ply level scaling ( Fig.…”
Section: Applications Of Similitude Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many articles [33,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] showed that stacking sequence is a key parameter in scaling composite materials. There are three scaling approaches, namely ply level scaling ( Fig.…”
Section: Applications Of Similitude Methodsmentioning
confidence: 99%
“…The choice of the scaling strategy has significant consequences on the response of the composite specimen. This choice is studied in many works [68][69][70][71][72] in which it is demonstrated that ply level scaling applied only to the thickness or to all the geometric dimensions (also known as one-and three-dimensional scaling, respectively) leads to a decreasing tensile strength with increasing size. Such behavior is due to the increased severity of edge delamination and debonding, creating stress concentrations that lower the strength of hybrid materials.…”
Section: Applications Of Similitude Methodsmentioning
confidence: 99%
“…Johnson et al. 8 undertook a series of tensile tests on scaled carbon fiber reinforced samples based on both epoxy and PEEK matrices. The authors noted that the strength of the composite samples increased with increasing specimen size.…”
Section: Introductionmentioning
confidence: 99%
“…A size effect can be defined as a change in strength with specimen dimensions [1]. Unnotched specimens of continuous fibre reinforced laminates have been extensively tested [2][3][4][5][6], emphasizing the volume-scaling effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unnotched quasi-isotropic specimens [3,6] have also been tested to study the size effects, and free edge delaminations were identified to be one of the potential failure modes [6]. These free edge effects have been previously studied [7][8][9].…”
Section: Introductionmentioning
confidence: 99%